Perfluoroalkyl substance pollutants activate the innate immune system through the AIM2 inflammasome - Li-Qiu Wang (Nature Portfolio, 2021)
The double-stranded DNA receptor AIM2 is able to sense the environmental pollutant perfluorooctane sulfonate, a prototypical perfluoro-alkyl substrate. Activation of the AIM2 pathway leads to inflammation and tissue damage via IL-1β secretion and pyroptosis of affected innate immune cells.